1992
DOI: 10.1080/09540129208253101
|View full text |Cite
|
Sign up to set email alerts
|

Situational factors and thought processes associated with unprotected intercourse in heterosexual students

Abstract: Heterosexual students were asked to recall two sexual encounters from the preceding six months: one in which they had unprotected intercourse ('unsafe' encounter) and one in which they resisted a strong temptation to have unprotected intercourse ('safe' encounter). The aims were to record justifications for unprotected intercourse that respondents had given themselves during the unsafe encounter and to identify factors that distinguished between the encounters. In respondents recalling an unsafe encounter (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 21 publications
3
38
0
1
Order By: Relevance
“…Consistent with this interpretation, we found that the total effect of alcohol use on condom use was -.04 and not significant, but that its direct effect after controlling for partner intimacy ratings was -.17 and significant. Findings reported by Gold et al (1992), who reported the only significant within-persons effect for condom use among the previously reviewed stud ies, lend further credence to this interpretation. The key difference between their study and the remaining studies was that they controlled for partner intimacy by limiting their analyses to the subset of individuals who had equally intimate partners across the two occasions.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with this interpretation, we found that the total effect of alcohol use on condom use was -.04 and not significant, but that its direct effect after controlling for partner intimacy ratings was -.17 and significant. Findings reported by Gold et al (1992), who reported the only significant within-persons effect for condom use among the previously reviewed stud ies, lend further credence to this interpretation. The key difference between their study and the remaining studies was that they controlled for partner intimacy by limiting their analyses to the subset of individuals who had equally intimate partners across the two occasions.…”
Section: Discussionsupporting
confidence: 58%
“…Gold et al (1992) found that the level of intoxication reported on two different sexual encounters was associated with whether the respondent had engaged in unprotected sex during those encounters. Graves and Leigh (1995) found no significant relationship between intoxication and unprotected sex when they compared the proportion of unprotected sexual encounters under the influence of alcohol vs. those without alcohol, even though they noted a global association between heavy-drinking and unprotected sex.…”
Section: Nih Public Accessmentioning
confidence: 97%
“…Desiderato & Crawford (1995) found that the frequency and quantity of college students' alcohol consumption was associated with the number of sexual partners in the last 11 weeks, and that alcohol consumption preceded the last occurrence of sex. Gold, Karmiloff-Smith, Skinner, and Morton (1992) found intoxication to be a predictive factor at all points in casual sexual encounters (from the beginning of the encounter to the period of sexual contact); the highest level of intoxication occurred at the start of sexual intercourse. Moreover, males and females were found to be more likely to consume alcohol when they were less well acquainted with their partner (Temple & Leigh, 1992).…”
Section: Social Predictorsmentioning
confidence: 99%